A Coptic magical name in a Pannonian phylacterion - Fehér, Bence (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
A silver lamella was found in Aquincum (1927/28), in a burial site which could be easily dated to the latest Trajan or early Hadrian era, but it was published defectively, misread and misinterpreted. Several attempts at re-interpretation in the 1990s and 2000s succeeded only partially. The reading I propose contains distinct textual units beginning with characters (among them hieroglyphs), and a Coptic magical logos (παχνουφις). In my opinion, the phylacterion was meant to give protection in the next world, and the writer of the spell was well acquainted with the Egyptian magical traditions.